2000
DOI: 10.1097/00007691-200008000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Caffeine as an In Vivo Probe for CYP1A2 Using Measurements in Plasma, Saliva, and Urine

Abstract: Twenty-five healthy volunteers were given 100 mg caffeine orally and several estimates of cytochrome P450 1A2 (CYP1A2) activity were evaluated. The validation was performed by correlation of different parameters in plasma, saliva, and urine to two measures of caffeine clearance, CL(oral) and CL(137X-->17X) that served as standards of reference. Two subjects were excluded because of noncompliance with a caffeine-free diet. In the remaining 23 subjects, both plasma and saliva total clearances of caffeine were hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
99
0
8

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(112 citation statements)
references
References 41 publications
1
99
0
8
Order By: Relevance
“…The metabolic pathways of caffeine are complex but involve the formation of three principal metabolites: theobromine (3,7-dimethyl xanthine [37X]), theophylline (1,3-dimethylxanthine [13X]), and paraxanthine (1,7-dimethylxanthine [17X]). Each of these metabolites are primarily formed by cytochrome (CYP) P450 1A2 (Carrillo et al, 2000). Conversion to the 17X metabolite comprises about 80% of the metabolic pathway for caffeine.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The metabolic pathways of caffeine are complex but involve the formation of three principal metabolites: theobromine (3,7-dimethyl xanthine [37X]), theophylline (1,3-dimethylxanthine [13X]), and paraxanthine (1,7-dimethylxanthine [17X]). Each of these metabolites are primarily formed by cytochrome (CYP) P450 1A2 (Carrillo et al, 2000). Conversion to the 17X metabolite comprises about 80% of the metabolic pathway for caffeine.…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic pathways to the 37X and 13X metabolites are also influenced by CYP2E1 (Sinues et al, 1999). Caffeine has become popular as a metabolic probe for CYP1A2 activity in humans (Carrillo et al, 2000); it is one of the major P450 cytochromes in the liver and accounts for 15% of the total P450 content.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in a study involving 25 patients undergoing hepatectomy, significant correlations were found between in vivo parameters of CYP1A2 activity, being caffeine clearance and paraxanthine/caffeine ratios (3 and 6 h post-dose) in oral fluid or plasma, and in vitro parameters, being caffeine 3-demethylation and relative CYP1A2 content in liver microsomes [13]. Since then, the validity of oral fluid for CYP1A2 phenotyping was corroborated by several other studies [81][82][83][84][85][86][87] and, consequently, this approach has been widely applied to assess CYP1A2 activity in various settings [61,85,86,[88][89][90][91][92][93][94][95][96][97][98].…”
Section: Oral Fluidmentioning
confidence: 81%